If Jeremiah wrote it, it must be OK: on the attribution of lamentations to Jeremiah in early rabbinic texts - J. Kalman (Acta Theologica)
Despite the absence of any formal attribution of the book of Lamentations to the prophet Jeremiah in the Hebrew Bible, the rabbis of the Talmudic period chose to perpetuate and reinforce this idea. The question explored is how this benefited them. Using Jorge Gracia’s discussion of the “pseudo-historical author,” the influence of the rabbinic assumption of Jeremiah’s authorship of Lamentations on their exegesis of the book is explored. The rabbis were troubled by a number of theologically challenging verses and the claim of authorship opened the door to their use of the book of Jeremiah to explain away these difficulties.